Characteristics of echolocation clicks in southern resident killer whales (Orcinus orcas) - Chang, Sofia (Friday Harbor Labs, 2011)
Odontocetes rely on echolocation clicks to navigate, forage and communicate. As such, understanding the characters of click shall help understanding whale communication. Southern resident killer whales of the North Pacific Ocean are recorded echolocating at Lime Kiln State Park and characteristics of the echolocation clicks are explored. This study aims to describe the nature of killer whale vocalization by analyzing their calls and echolocation characteristics. Click train duration, number of clicks and duration of individual clicks are measured and tested against the hypothesis that they should follow a normal curve. Results mostly confirmed previous studies of the echolocation click’s predominant characteristics in terms of click train duration of ( <10 seconds), number of clicks in a click train ( 0-50 clicks) and individual click duration (<2ms). However, results failed to accept the hypothesis that the characteristics should follow a normal distribution. Suspected reason for such result lies in limitations of the acoustic data’s collection methods, such as immobility of the hydrophones and unknown location of the killer whales respect to hydrophones. In addition, factors of conducting a short-term bioacoustic study are discussed.